Superstrings and Loop Quantum Gravity are Two Sides of the Same Golden Coin - Elnaschie, M. S. (European Journal of Applied Sciences, 2022)
The general framework of the paper is to rekindle the profound mathematical and philosophical revelations of the Ancient Greek-Egyptian school of Alexandria where the Egyptian, Persian, Indian, Chinese, Greek, Roman, Islamic and Arabic civilizations melted together to form a shrine of science, art and wisdom culminating in the Platonic-Pythagorean golden mean number system utilized in E-Infinity Cantorian spacetime of present modern science. Based on the above, we introduce a new universal mean which seems not only to have numerous applications in statistics, but also goes as far as showing that not only superstrings and loop quantum gravity are simply two sides of a certain harmonic golden coin. In fact, the work goes far beyond that by encompassing science, art and consciousness into a magnificent single entity.